Disentangling the dynamic interplay between muscle damage and energetics in male boxers during a short training block - Obmiński, Zbigniew; Crewther, Blair T; Cook, Christian J (Biology of Sport, 2024)
Boxing is a combat sport linked to muscle damage (e.g., soreness, rising creatine kinase [CK]) and energetic biomarkers (e.g., urea, glucose). These factors have not, however, been examined dynamically in terms of day-to-day, lagged and reciprocal effects during normal training. This study investigated the dynamic interplay between muscle damage and energetics in male boxers during a short training block. Thirteen amateur boxers were monitored over 16 consecutive days during early-season training. The participants were assessed each morning for plasma CK, urea, glucose, and creatinine (days 1 and 16 only) concentrations, before self-reporting muscle soreness (1–10 scale). Within-person contemporaneous (lag-0) and temporal (lag-1) networks were estimated using multilevel vector autoregression. Muscle soreness, CK, urea, and glucose presented different trajectories with training, but with some heterogeneity reflecting within-person variances (47% to 78%). The contemporaneous network yielded a significant positive edge (or correlation) between CK and soreness (r = 0.44), along with negative CK-glucose and glucose-urea edges. More significant edges emerged in the temporal network, with soreness linked to CK (r = 0.19), glucose (r = -0.28) and urea (r = 0.22), whilst the CK-glucose edge sign switched. In summary, daily fluctuations in muscle damage and energetic activity, which presented in a normal physiological range, were highly variable among boxers during early-season training. Within-person networks indicated some interrelatedness between CK, soreness, urea, and glucose, although the nature and presence of these relationships were contingent on temporal ordering. These inconsistences reflect the pleiotropy of energetic biomarkers in training and recovery.